Clinical Predictors of Progressive Hemorrhagic Injury in Children with Mild Traumatic Brain Injury - Di, Guangfu; Liu, Hua; Jiang, Xiaochun; Dai, Yi; Chen, Sansong; Wang, Zhichun; Liu, Hongyi (Frontiers in Neurology, 2017)
OBJECTIVE: Traumatic brain injury (TBI) occurs commonly in children. Repeat computed tomography (CT) follow up of TBI patients is often scheduled to identify progressive hemorrhagic injury (PHI). However, the utility of repeated CT scans, especially in children with mild TBI (Glasgow Coma Scale [GCS] scores of 13–15), has been debated. The purposes of the present study were to identify clinical predictors of PHI in children with mild TBI and to clarify relevant clinical factors via radiological examination. METHODS: From 2014 to 2016, we retrospectively enrolled children <15 years of age with mild TBI. We recorded age, sex, GCS scores on admission, causes of head injury, timing of initial CT, any loss of consciousness, vomiting and seizure data, and type of TBI. Based on repeat CT findings, patients were dichotomized into either a PHI group or a non-PHI group. Also, clinical data were comparatively reviewed. Multivariate logistic regression analysis was used to identify clinical predictors of PHI. RESULTS: Of the 175 enrolled children, 15 (8.6%) experienced PHI. Univariate analysis revealed that GCS score on admission, cause of head injury, vomiting, seizure, and TBI type were associated with PHI. Multivariate logistic regression analysis showed that a GCS score of 13 and epidural hemorrhage (EDH) were independently associated with PHI (hazard ratio=0.131, P=0.018; hazard ratio=6.612, P=0.027, respectively). CONCLUSIONS: A GCS score of 13 and EDH were associated with PHI. These factors should be considered when deciding whether to repeat CT on children with mild TBI. Key words: Mild traumatic brain injury, Children, Progressive hemorrhagic injury. INTRODUCTION Traumatic brain injury (TBI) is common in children and is an important cause of disability and morbidity1. The incidence of TBI in children is estimated to be 250 per 100,000 per year. TBI accounts for >7,000 deaths and 600,000 emergency department visits annually among children in the United States2. The vast majority of TBIs in children are mild, requiring no specific therapy and associated with no sequelae1. However, a small proportion of patients presenting with mild TBI develop progressive hemorrhagic injury (PHI). Therefore, it is important to recognize and intervene early in PHI to improve prognosis. Computed